Modulation of the Acidity of HY, HBETA, and HZSM-5 Zeolites by Lanthanum Incorporation for Selective Gasoline Desulfurization in the FCCRiser - Santos, Ronaldo C.; Silva, Anderson Cerqueira dos Santos; Lam, Yiu Lan; Ferreira, Jose Marcos Moreira; Ballesteros-Plata, Daniel; Rodríguez-Castellón, Enrique; Martínez Arribas, Agustin; Pontes, Luiz A. M. (Wiley, 2025)
This study evaluates the incorporation of lanthanum into zeolites Y, Beta, and ZSM-5 to promote the desulfurization of a gasoline stream directly in the riser of a fluid catalytic cracking (FCC) process. The catalysts were prepared using wet impregnation and characterized by X-ray diffraction (XRD) (crystallinity and phase integrity), XRF (La content and Si/Al ratio), X-ray photoelectron spectroscopy (XPS), solid state nuclear magnetic resonance (NMR) of 29Si and 27Al, N2 adsorption, high-resolution transmission electron microscopy (HRTEM), temperature-programmed desorption of ammonia (TPD-NH3), Fourier-transform infrared spectroscopy (FTIR), and pyridine chemisorbed FTIR (FTIR-Py). Catalytic tests were conducted in a tubular reactor, using a mixture of cyclohexane and thiophene (20000 ppm) at 773 K and 1.3 atm. Catalytic activity was assessed in a fixed-bed reactor using a cyclohexane/thiophene feed, and product selectivities were quantified by gas chromatography with flame ionization and sulfur chemiluminescence detectors. The addition of lanthanum altered the acidity of the catalysts, reducing the total density of acid sites while increasing the strength of Lewis acid sites. The protonated zeolites, particularly HY, facilitated sulfur removal, achieving a 91% selectivity for H2S through secondary hydrogen transfer reactions. In contrast, the lanthanum-modified zeolites enhanced thiophene alkylation and condensation reactions, as evidenced by the selectivity observed in La/BEA and La/ZSM-5, which reached 15%. The results indicated that incorporating lanthanum changes the desulfurization profile, making the catalysts more selective for forming higher molecular weight sulfur compounds, thereby shifting the products toward the FCC diesel range.
Keywords: Catálisis heterogénea; Petróleo - Refino; Industria petroquímica; Materiales porosos; Zeolitas; Cracking; Desulfurization; FCC; Lanthanum; Zeolites